Les Effets Macroéconomiques Des Prélèvements Fiscaux Sur L’investissement En Algérie - Mahtout, Samir (مركز البصيرة للبحوث والاستشارات والخدمات التعلمية, 2019)
This article aims to assess the impact of the tax structure on investment in Algeria. The approach used concerns an estimation through a vector error correction model (VECM) and this from the annual data covering the period 1970- 2016. The results obtained generally reveal the existence of a Cointegrating relationship (positive and significant) in the means and long term between tax variables and GFCF. However, in the short term, state tax revenues do not significantly influence investment, except for oil revenues. Our results also show that current tax is in aria to initiate a dynamic of economic growth through the financing of the state budget because of a marginal return on tax revenues.
Keywords: الجزائر -- السياسة الاقتصادية -- الضرائب -- الاقتصاد الكلي -- الاستثمار